In operando X-ray absorption spectroscopy study of charge rate effects on the atomic environment in graphene-coated Li-rich mixed oxide cathode. (15th May 2016) - Kim, Taehoon; Song, Bohang; Lunt, Alexander J.G.; Cibin, Giannantonio; Dent, Andrew J.; Lu, Li; Korsunsky, Alexander M.
Abstract: Li2 O extraction from the electrode material is known to be a dominant mechanism of irreversible battery capacity loss in the first cycle. The extraction mechanism of the Li + ions shows dependence on the charge rate. Here for the first time we report the difference in the electrochemical behavior at two different charge rates (0.125 C vs 0.5 C) observed using novel design transmission coin cells in the graphene-coated Li(Li0.2 Mn0.54 Ni0.13 Co0.13 )O2 cathode by in operando X-ray absorption spectroscopy (XAS). The results obtained from Mn, Co, and Ni atom XANES/EXAFS demonstrate that, whilst during fast charge Li2 O extraction is localized to the lithium slab in the crystal structure, the delithiation is deeper at the slower charge rate, when Li + ions are removed from both the transition metal and lithium layers. In the slow charge cell, NiO bond splitting resulting from the Jahn-Teller distortion were clearly identified at approximately 4.224 V when a sudden rise in the bond length was observed in the EXAFS analysis of MnO and CoO bonds. The results demonstrate the power of using the novel cell design for transmission in operando XAS. Graphical abstract: Highlights: First in situ EXAFS study of charge rate dynamic in graphene-coated Li(Li0.2 Mn0.54 Ni0.13 Co0.13 )O2 cathode is reported. Distinct charge compensation in Li-rich Mn-based cathode is revealed. Full battery capacity under slow charging is attained with distinct local-atomic environment separation at 4.2 V. Jahn-Teller effect NiO bond splitting during slow charging was successfully evaluated by EXAFS.